Respostas

2014-07-02T09:12:42-03:00
Ax²+bx+c=0
x²-8x+15=0
Δ=b²-4*a*c
Δ=(-8)²-4*1*15=64-60=4 -> √4=2
x'=(-b+√Δ)/(2*a)
x'=[-(-8)+2]/2=5
x''=(-b-√Δ)/(2*a)
x''=[-(-8)-2]/2=3

Resposta: 5 e 3
Espero ter ajudado.

2014-07-02T09:19:30-03:00
qual a resposta ?  ×²-8×+15=0 

x² - 8x + 15 = 0
a = 1
b = -8
c = 15
Δ = b² - 4ac
Δ = (-8)² - 4(1)(15)
Δ = 64 - 60
Δ = 4 --------------------------------------√4 = 2
se
Δ > 0
então (baskara)
x = -b - + 
√Δ/2a
x' = -(-8) - √4/2(1)
x' = + 8 - 2/2
x' = 6/2
x' = 3
e
x" = -(-8) + √4/2(1)
x" = + 8 + 2/2
x" = 10/2
x" = 5

V = { 3,5}